Kontribusi Minat Dalam Peningkatan Hasil Belajar Filsafat Pendidikan - Ramli Abdullah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2014)
Learning is change of somebody ability and defensible in certain range of time. Various growth that happened in learning that, like behaviour change after student somebody getting various experience at various situation learn the itself, so that from various that experience will cause the change process that happened in x'self of student somebody. Result learn is entire efficiency and its result is which reached for by student of through study process and specified with the number measured by pursuant to test of result of learning. That result learn which is reached for by student after experiencing of experience learn in eye of learning of Education Philosophy followed of. That study activity to eye of related/relevant kuliah Education Philosophy once with the enthusiasm problem, motivate and mount the dread, so that can succeed in learning eye of certain learning Education Philosophy, hence student somebody shall have the enthusiasm to eye of the learning Education Philosophy, because that enthusiasm will influence the somebody motivation to be diligent in learning. such hence student enthusiasm in learning in this article is student enthusiasm to eye of kuliah of Education Philosophy, because student interested to a eye of learning of Education Philosophy so that he will learn easily and please in activity of study of eye of learning of Education Philosophy which following. Kata Kunci: Minat, Belajar, Filsafat Pendidikan